2002
DOI: 10.1016/s0960-9822(02)01180-6
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Crumbs Is Required to Inhibit Light-Induced Photoreceptor Degeneration

Abstract: Mutations in the human transmembrane protein CRB1 are associated with severe forms of retinal dystrophy, retinitis pigmentosa 12 (RP12), and Leber's congenital amaurosis (LCA). The Drosophila homolog, crumbs, is required for polarity and adhesion in embryonic epithelia and for correct formation of adherens junctions and proper morphogenesis of photoreceptor cells. Here, we show that mutations in Drosophila crumbs result in progressive, light-induced retinal degeneration. Degeneration is prevented by expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
192
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(202 citation statements)
references
References 28 publications
8
192
1
1
Order By: Relevance
“…Experiments on fruit fly Crumbs showed that the extracellular domain played an important role in prevention against light damage (Johnson et al, 2002). Here, we show that the amino acid substitution in Crb1 C249W caused loss of protection against the effects of light (increased incidence of retinal folds and upregulation of GFAP at foci, and low levels of retinal Pttg1 transcripts).…”
Section: Crb1mentioning
confidence: 61%
“…Experiments on fruit fly Crumbs showed that the extracellular domain played an important role in prevention against light damage (Johnson et al, 2002). Here, we show that the amino acid substitution in Crb1 C249W caused loss of protection against the effects of light (increased incidence of retinal folds and upregulation of GFAP at foci, and low levels of retinal Pttg1 transcripts).…”
Section: Crb1mentioning
confidence: 61%
“…In addition, human homologues of Crb are implicated in retinitis pigmentosa and Leber congenital amaurosis, two heritable forms of human disease of photoreceptor degeneration (21)(22)(23)(24). In Drosophila, crb photoreceptors also degenerate under intense lighting conditions (25), resembling the phenotype in human diseases. It would be of interest to find out whether mutations in the human homologues of Sdt, Dlt, and possibly aPKC lead to photoreceptor degeneration.…”
Section: Discussionmentioning
confidence: 95%
“…This issue may have bearing on human retinal dystrophies as the phenomenon of retinal degeneration resulting from stable rhodopsin/arrestin complexes has been documented in rodent animal models [236,237]. Mutations in Drosophila crumbs and its human homolog lead to light-induced retinal degeneration, but the mechanisms underlying these retinal degenerations are poorly understood [238,239]. The Drosophila retinal pigment cells appear to function similarly to human RPE cells in the generation of the chromophore [81], and many genetic defects in human RPE cells are known to cause photoreceptor cell degeneration.…”
Section: Discussionmentioning
confidence: 99%